Answers

2015-04-27T19:45:01+05:30
3x^2-x^3-3x+5 
  also , -x^3+3x^2-3x+5
x^2+x-1 ) -x^3+3x^2-3x+5 ( -x+4

               - x^3 -x^2+x           
               ________________             

                      4x^2-4x+5
                      4x^2 - 4x-4
                  _______________
                                 -8x+9                  

  
 clearly , remainder = -8+9
             quotient = -x+4
   using  division algorithm ,
    a = b*q+r
       = (x^2+x-1)(-x+4)-8+9
      = 
 -x^3+3x^2-3x+5 
    also , 3x^2-x^3-3x+5 ( dividend )

          
0
2015-04-28T00:54:36+05:30
the answer is in attached pic
0